FACTORS CAUSING AIR POLLUTION AND ITS IMPACT ON PUBLIC HEALTH - Sari, Vany Armiantika (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Air pollution is one of the environmental damages, in the form of reduced air quality due to the entry of harmful chemical compounds into the air or the earth's atmosphere. It is known that there are several impacts of air pollution, including: acid rain which can affect the quality of surface water, damage to plants and ecosystems, as well as the greenhouse effect which causes the phenomenon of global warming, changes in the life cycle of flora and fauna, and damage to the ozone layer. Methods: The method used in this research is literature study or library research. Data collection techniques used in this research process by collecting several sources from journals. Results: The causes of air pollution and its impact on human health come from natural factors and human activities. Conclusion: Excessive ingalation of polluted air can pose a risk of various health problems for humans.